Transgenerational deep sequencing revealed hypermethylation of hippocampal mGluR1 gene with altered mRNA expression of mGluR5 and mGluR3 associated with behavioral changes in Sprague Dawley rats with history of prolonged febrile seizure. - Oluwole Ojo Alese; Musa V Mabandla (PLoS ONE, 2019)
The impact of febrile seizure has been shown to transcend immediate generation with the alteration of glutamatergic pathway being implicated. However, transgenerational effects of this neurological disorder particularly prolonged febrile seizure (PFS) on neurobehavioral study and methylation profile is unknown. We therefore hypothesized that transgenerational impact of prolonged febrile seizure is dependent on methylation of hippocampal mGluR1 gene. Prolonged febrile seizure was induced on post-natal day (PND) 14, by injecting lipopolysaccharide (LPS; 217μg/kg ip) and kainic acid (KA; 1.83 mg/kg ip). Sucrose preference test (SPT) and Forced swim test (FST) were carried out in the first generation (F0) of animals at PND37 and PND60. The F0 rats were decapitated at PND 14, 37 and 60 which corresponded to childhood, adolescent and adulthood respectively and their hippocampal tissue collected. The second generation (F1) rats were obtained by mating F0 generation at PND 60 across different groups, F1 rats were subjected to SPT and FST test on PND 37 only. Decapitation of F1rats and collection of hippocampal tissues were done on PND 14 and 37. Assessment of mGluR5 and mGluR3 mRNA was done with PCR while mGluR1 methylation profile was assessed with the Quantitative MassARRAY analysis. Results showed that PFS significantly leads to decreased sucrose consumption in the SPT and increased immobility time in the FST in both generations of rats. It also leads to significant decrease in mGluR5 mRNA expression with a resultant increased expression of mGluR3 mRNA expression and hypermethylation of mGluR1 gene across both generations of rats. This study suggested that PFS led to behavioral changes which could be transmitted on to the next generation in rats.